Surgical vs. Non-Surgical Management of Mandibular Condyle Fractures in Adolescent - Abdurrahman Adirhesa; Carolina Cita Brilliani; Fredy Mardiyantoro (Majalah Biomorfologi, 2025)
Highlights Non-surgical treatments can involve various appliances. However, all non-surgical treatments are typically supplemented with mouth-opening exercises. Surgical treatments usually consist of open reduction and internal fixation, which can be implemented using various anatomical approaches.   Abstract Background: Mandibular condyle fractures are common among adolescents, often resulting from trauma such as falls or road traffic accidents. These fractures, which involve the articular surface of the mandible, can lead to complications like malocclusion, restricted mouth opening, and temporomandibular joint dysfunction. Treatment for mandibular condyle fractures varies, with non-surgical management, including closed reduction and functional therapy, often favored for its less invasive nature, especially in growing adolescents. Surgical interventions, such as open reduction and internal fixation, are considered for more complex fractures or when non-surgical methods fail. However, the decision between surgical and non-surgical treatment remains contentious, particularly in adolescents, whose condylar fractures might heal better due to the regenerative capacity of their growing bones. Objective: This review aimed to compare the outcomes of surgical and non-surgical management of mandibular condyle fractures. Material and Method: This review was conducted by searching the Scopus database for case reports published between 2014 and 2024, which described either surgical or non-surgical treatment of adolescent mandibular condyle fractures. Result: A total of 7 case reports were included, highlighting the use of various treatment approaches. Non-surgical methods, including functional appliances and mouth-opening exercises, showed promising results, with improved mouth opening and condylar remodeling. Similarly, surgical approaches, though more invasive, resulted in good functional and aesthetic outcomes, with minimal complications when proper anatomical understanding was applied. Conclusion: Both non-surgical and surgical approaches can be used to treat condylar fractures in adolescents, provided that proper evaluation, planning, and a thorough understanding of the condyle's anatomy and surrounding tissue are ensured.